Improving Electronic Document Control Approval Process Through E-Certification - Mohamad, Effendi; Rahmat, Rashitah; Mohamad, Nor Akramin; Jaafar, Roshidah; Yuniawan, Dani; Ito, Teruaki (Penerbit UTeM, 2019)
This paper analysed factors that influenced the document rejection rate in a semiconductor manufacturing facility. One of the factors that affected document rejection rate was a wrongly written process parameter which caused failure in data extraction. This resulted in many processes on the manufacturing floor to be placed on hold, hence, delaying product delivery to customers. Through current approval workflow, specification writers are required to be trained and certified prior to submitting any revised or new documents for approval. It is important to have the revised specifications approved on first time submission to ensure prompt document update. Hence, the main idea of this work was to improve the approval workflow through reducing number of documents rejection rate during the approval process. This approval workflow was conducted through electronic certification using an electronic document management system (e-DMS). A 3-level electronic certification process for specification writers was introduced to ensure that only certified writers could revise or edit any specifications. The new certification process was successfully implemented and the data were closely monitored for the period of 6 months. The outcome showed 4% improvement on document rejection rate during the approval process. The number of documents submitted for approval within the same period was also increased by 28%.